Preparing Educators to Teach in a Digital Age - Mohsen Keshavarz (Athabasca University Press, 2021)
This article describes the practical implementation of parts of Teaching in a Digital Age: Guidelines for Designing Teaching and Learning by A.W. Bates (2015) in a course for educators in Austria and the development of medical education for universities in Iran. With the publication of the second edition of Teaching in a Digital Age in 2019, the authors show the impact of the book in training educators and developers of educational content. This note from the field emphasizes the benefits of making informed decisions about educational technologies using Bates’ (2015) SECTIONS model and of learning about massive open online courses (MOOCs) and how to work with them using his book.